Bulk Ceramic Composites Derived from a Preceramic Polysilazane with Alumina and Zirconia Fillers1. Issue 5 (21st January 2013) - Konegger, Thomas; Liersch, Antje; Gierl, Christian; Scheffler, Michael
Abstract Bulk composites for the production of green‐machinable, complex‐shaped ceramic parts with tailorable properties for applications under mechanical stress are fabricated by a novel combination of a poly(vinyl)silazane‐derived ceramic matrix with Al2O3 or ZrO2 fillers. Green‐machinable composites were produced by coating of the filler powders with the preceramic polymer, followed by subsequent warm‐pressing. The final ceramic materials are obtained by a thermal conversion process. A systematic variation of preceramic polymer content, pressure during warm‐compaction, or pyrolytic conversion temperature is used to identify the main factors responsible for differences in densification behavior, microstructure, composition, and mechanical properties. The procedure of composite powder preparation as well as the optimization of the subsequent warm‐pressing step are found to be decisive in the successful production of crack‐free bulk ceramic composites.